2024
DOI: 10.1073/pnas.2309243121
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus proteases trigger eosinophil-mediated skin inflammation

Sabrina N. Kline,
Nicholas A. Orlando,
Alex J. Lee
et al.

Abstract: Staphylococcus aureus skin colonization and eosinophil infiltration are associated with many inflammatory skin disorders, including atopic dermatitis, bullous pemphigoid, Netherton’s syndrome, and prurigo nodularis. However, whether there is a relationship between S. aureus and eosinophils and how this interaction influences skin inflammation is largely undefined. We show in a preclinical mouse model that S. aureus epicutaneous exposure induced eosino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 83 publications
(151 reference statements)
0
2
0
Order By: Relevance
“…Recent evidence has demonstrated that, in the skin of a preclinical mouse model, eosinophilrecruiting chemokines (and eosinophil infiltration) are induced after Staphylococcus aureus epicutaneous exposure, the IL-36α-IL-36R pathway is involved [194].…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence has demonstrated that, in the skin of a preclinical mouse model, eosinophilrecruiting chemokines (and eosinophil infiltration) are induced after Staphylococcus aureus epicutaneous exposure, the IL-36α-IL-36R pathway is involved [194].…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence has demonstrated that, in the skin of a preclinical mouse model, eosinophil-recruiting chemokines (and eosinophil infiltration) are induced after Staphylococcus aureus epicutaneous exposure, and the IL-36α-IL-36R pathway is involved [ 194 ].…”
Section: Discussionmentioning
confidence: 99%